Artifacts in Musculoskeletal MR Imaging - Singh, Dinesh R.; Chin, Michael S.M.; Peh, Wilfred C.G. (Seminars in Musculoskeletal Radiology, 2014)
MR imaging has become an important diagnostic tool in the evaluation of a vast number of pathologies and is of foremost importance in the evaluation of spine, joints, and soft tissue structures of the musculoskeletal system. MR imaging is susceptible to various artifacts that may affect the image quality or even simulate pathologies. Some of these artifacts have gained special importance with the use of higher field strength magnets and with the increasing need for MR imaging in postoperative patients, especially those with previous joint replacements or metallic implants. Artifacts may arise from patient motion or could be due to periodic motion, such as vascular and cardiac pulsation. Artifacts could also arise from various protocol errors including saturation, wraparound, truncation, shading, partial volume averaging, and radiofrequency interference artifacts. Susceptibility artifact occurs at interfaces with different magnetic susceptibilities and is of special importance with increasing use of metallic joint replacement prostheses. Magic angle phenomenon is a special type of artifact that occurs in musculoskeletal MR imaging. It is essential to recognize these artifacts and to correct them because they may produce pitfalls in image interpretation.
Keywords: chemical shift artifact; magnetic resonance imaging; motion artifact; protocol-error artifacts; susceptibility artifact